2021
DOI: 10.1002/acm2.13482
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach based on deep learning and level set formulation for liver segmentation in CT images

Abstract: Accurate liver segmentation is essential for radiation therapy planning of hepatocellular carcinoma and absorbed dose calculation. However, liver segmentation is a challenging task due to the anatomical variability in both shape and size and the low contrast between liver and its surrounding organs. Thus we propose a convolutional neural network (CNN) for automated liver segmentation. In our method, fractional differential enhancement is firstly applied for preprocessing. Subsequently, an initial liver segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A method using Mask R-CNN with soft parameter selection was proposed by Dandil et al [37]. Gong et al [38] introduced a fractional differential enhancement-based CNN model. Senthilvelan and Jamshidi [39] introduced and automated workflow for liver segmentation using a cascaded approach (PADLLS).…”
Section: Related Workmentioning
confidence: 99%
“…A method using Mask R-CNN with soft parameter selection was proposed by Dandil et al [37]. Gong et al [38] introduced a fractional differential enhancement-based CNN model. Senthilvelan and Jamshidi [39] introduced and automated workflow for liver segmentation using a cascaded approach (PADLLS).…”
Section: Related Workmentioning
confidence: 99%
“…17 Kawula et al trained a model using an in-house algorithm, and demonstrated DSC of 0.87, 0.97, and 0.89 for prostate, bladder, and rectum, respectively. 18 In addition to prostate cancer, CT-based DL auto-segmentation models have also been reported for other disease sites, such as brain, 19,20 head and neck, 21,22 lung, [23][24][25][26] breast, 27 esophagus, 28 liver, [29][30][31] pancreas, 32 bladder, 33 and gynecological cancers. 34,35 While the prior studies have demonstrated the feasibility of constructing DL models to automate the tedious contouring task in prostate treatment planning, the applicability of each model is limited by clinical protocol, particularly the immobilization method which can affect the shape and position of key organs.…”
Section: Introductionmentioning
confidence: 99%
“…trained a model using an in‐house algorithm, and demonstrated DSC of 0.87, 0.97, and 0.89 for prostate, bladder, and rectum, respectively 18 . In addition to prostate cancer, CT‐based DL auto‐segmentation models have also been reported for other disease sites, such as brain, 19,20 head and neck, 21,22 lung, 23–26 breast, 27 esophagus, 28 liver, 29–31 pancreas, 32 bladder, 33 and gynecological cancers 34,35 …”
Section: Introductionmentioning
confidence: 99%
“…Based on the presence of mutations, the authors defined low and high fibroblasts activation classes and, on this variable, they analyzed HCC sensitivity to chemotherapy. Their results showed that patients with high activation of cancer-associated fibroblasts had increased response to chemotherapy.It is also worth to say that many authors have recently published different DL models to perform segmentation of liver cancer and vacularization with the aim to develop a tool useful for physicians to plan liver cancer treatment(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). However, their results are limited to a comparison of accuracy between the proposed model and manual segmentation or segmentation performed by other models, without any proposed practical applications in clinical setting.…”
mentioning
confidence: 99%